Apolipoprotein A-I and A-I mimetic peptides: a role in atherosclerosis - Getz GS; Reardon CA (Dove Medical Press, 2011)
Godfrey S Getz, Catherine A ReardonThe University of Chicago, Department of Pathology, Chicago, IL, USAAbstract: Cardiovascular disease remains a major cause of morbidity and mortality in the westernized world. Atherosclerosis is the underlying cause of most cardiovascular diseases. Atherosclerosis is a slowly evolving chronic inflammatory disorder involving the intima of large and medium sized arteries that is initiated in response to high plasma lipid levels, especially LDL. Cells of both the innate and adaptive immunity are involved in this chronic inflammation. Although high plasma LDL levels are a major contributor to most stages of the evolution of atherosclerosis, HDL and its major protein apoA-I possess properties that attenuate and may even reverse atherosclerosis. Two major functions are the ability to induce the efflux of cholesterol from cells, particularly lipid-loaded macrophages, in the artery wall for transfer to the liver, a process referred to as reverse cholesterol transport, and the ability to attenuate the pro-inflammatory properties of LDL. The removal of cellular cholesterol from lipid-loaded macrophages may also be anti-inflammatory. One of the most promising therapies to enhance the anti-atherogenic, anti-inflammatory properties of HDL is apoA-I mimetic peptides. Several of these peptides have been shown to promote cellular cholesterol efflux, attenuate the production of pro-inflammatory cytokines by macrophages, and to attenuate the pro-inflammatory properties of LDL. This latter effect may be related to their high affinity for oxidized lipids present in LDL. This review discusses the functional properties of the peptides and their effect on experimental atherosclerosis and the results of initial clinical studies in humans.Keywords: apoA-I, mimetic peptides, HDL, anti-inflammatory, atherosclerosis